Phylogenomic and morphological relationships among the botryllid ascidians (Subphylum Tunicata, Class Ascidiacea, Family Styelidae) - Marie L. Nydam (Nature Portfolio, 2021)
Abstract Ascidians (Phylum Chordata, Class Ascidiacea) are a large group of invertebrates which occupy a central role in the ecology of marine benthic communities. Many ascidian species have become successfully introduced around the world via anthropogenic vectors. The botryllid ascidians (Order Stolidobranchia, Family Styelidae) are a group of 53 colonial species, several of which are widespread throughout temperate or tropical and subtropical waters. However, the systematics and biology of this group of ascidians is not well-understood. To provide a systematic framework for this group, we have constructed a well-resolved phylogenomic tree using 200 novel loci and 55 specimens. A Principal Components Analysis of all species described in the literature using 31 taxonomic characteristics revealed that some species occupy a unique morphological space and can be easily identified using characteristics of adult colonies. For other species, additional information such as larval or life history characteristics may be required for taxonomic discrimination. Molecular barcodes are critical for guiding the delineation of morphologically similar species in this group.